A 57.9-to-68.3GHz 24.6mW frequency synthesizer with in-phase injection-coupled QVCO in 65nm CMOS - Yi, Xiang (2013)
Under the influence of increasing demand for high-data-rate communication systems such as 60GHz band applications, the requirements of PLLs keep getting higher. In a mm-Wave direct-conversion transceiver, the quadrature LO signal generation is challenging. The conventional techniques to generate quadrature LO signals suffer from many problems. The method of using a divide-by-2 divider after a VCO with double LO frequency is popular in multi-GHz designs, but it is difficult to be realized at mm-Wave frequencies. Employing passive RC complex filters is another way to generate quadrature signals, but high power is required to compensate its loss. The conventional parallel-coupled QVCO seems to be a good choice for mm-Wave application. However, the approach suffers from poor phase noise. This work presents a fully integrated 57.9-to-68.3GHz frequency synthesizer, which employs an in-phase injection-coupled QVCO (IPIC-QVCO) to produce low-phase-noise quadrature signals with low power.